Hyper-CVAD regimen in combination with ofatumumab as frontline therapy for adults with Philadelphia chromosome-negative B-cell acute lymphoblastic leukaemia: a single-arm, phase 2 trial. Issue 7 (July 2020) - Jabbour, Elias; Richard-Carpentier, Guillaume; Sasaki, Yuya; Konopleva, Marina; Patel, Keyur; Roberts, Kathryn; Gu, Zhaohui; Wang, Feng; Huang, Xuelin; Sasaki, Koji; Short, Nicholas J; Jain, Nitin; et al.
Summary: Background: The addition of rituximab to intensive chemotherapy improves outcomes in patients with B-cell acute lymphoblastic leukaemia. Ofatumumab is an anti-CD20 monoclonal antibody that binds to the small extracellular loop of CD20 and has greater in vitro complement-mediated cytotoxicity than rituximab. In this study, we assessed the activity and safety of ofatumumab in combination with chemotherapy in patients with Philadelphia chromosome (Ph)-negative CD20-positive B-cell acute lymphoblastic leukaemia. Methods: This was a single-arm, phase 2 trial done at the MD Anderson Cancer Center (Houston, TX, USA). Patients with newly diagnosed, Ph-negative B-cell acute lymphoblastic leukaemia or lymphoblastic lymphoma with CD20 expression of at least 1% were eligible. Patients were treated with up to eight courses of the hyper-CVAD regimen (hyperfractionated cyclophosphamide, vincristine, doxorubicin, and dexamethasone) on courses 1, 3, 5, and 7 alternating with high-dose methotrexate and cytarabine on courses 2, 4, 6, and 8. Ofatumumab was administered on days 1 and 11 of courses 1 and 3 and on days 1 and 8 of courses 2 and 4 for a total of eight doses. The first dose of ofatumumab was 300 mg intravenously and all subsequent doses were 2000 mg intravenously. Patients received 30 courses of maintenance therapy with 6-mercaptopurine, vincristine, methotrexate, and prednisone (POMP), with four intensification courses (high-dose methotrexate plus L-asparaginase and hyper-CVAD plus ofatumumab on courses 6–7 and 18–19). The primary endpoints were event-free survival, overall response, and overall survival. All enrolled patients were included in the primary and safety analyses. The trial is registered with ClinicalTrials.gov, NCT01363128. Findings: Between Aug 26, 2011, and May 18, 2017, 69 patients (67 patients had B-cell acute lymphoblastic leukaemia and two had B-cell lymphoblastic lymphoma; median age 41 years [IQR 32-50]) were enrolled and treated, including 33 (48%) aged between 18 and 39 years. Nine (27%) of 33 patients had Ph-like acute lymphoblastic leukaemia. With a median follow-up of 44 months (26–53), 4-year event-free survival was 59% (95% CI 48–73); 69% (54–87) in adolescents and young adults aged 18–39 years. 4-year overall survival was 68% (58–81); 74% (60–91) in adolescents and young adults. The overall response rate was 98% (64 of 65 patients). The most common non-haematological grade 3 or 4 adverse events were infections (35 [54%] of 65 patients during induction and 53 [78%] of 68 patients during consolidation). Ten (14%) of 69 patients died in complete remission from sepsis (two [3%]), cardiac arrest (one [1%]), therapy-related acute myeloid leukaemia (two [3%]), and haematopoietic stem-cell transplantation complications (five [7%]). None of these deaths were considered related to ofatumumab treatment by the study investigators. Interpretation: The combination of hyper-CVAD plus ofatumumab is safe and active in adults with Ph-negative CD20-positive B-cell acute lymphoblastic leukaemia. Modifications of this regimen with the addition of novel monoclonal and bispecific antibody constructs targeting CD19 and CD22 might further improve outcomes and allow reduction in the intensity and duration of chemotherapy. Funding: Novartis.